Adolescent campus bullying and non-suicide self-injury: chain mediating effect of negative affect and sleep quality - Li Anan; Li Yaoyao; Xie Kunhang; Yuan Yong; Wang Xiaoyan; Li Lina; Lv Shaobo (Frontiers in Psychology)
AimThis study aimed to explore the chain mediating role of negative affect and sleep quality between campus bullying and non - suicidal self - injury (NSSI) among adolescents.Methods569 adolescents were selected through convenience sampling. Participants completed the Olweus Bully/Victim Questionnaire, Positive and Negative Affect Schedule, Pittsburgh Sleep Quality Index, and Adolescent Non - suicidal Self - injury Assessment Questionnaire.ResultsOur result showed significant positive correlations among campus bullying, negative affect, sleep quality and NSSI. Negative affect and sleep quality were identified as independent and sequential mediators in the relationship between campus bullying and NSSI.ConclusionThese findings elucidate the mechanisms linking campus bullying to NSSI, providing a preliminary basis for exploring the causal relationships among these variables. this study offers theoretical support for future research and inform the development of targeted interventions to reduce NSSI and improve the overall mental health of adolescents in China.